A New Method of Revealing Armourers' Marks. (2nd January 2019) - Williams, Alan; Edge, David; Grazzi, Francesco; Kardjilov, Nikolai
ABSTRACT: In this research, we performed radiographic experiments exploiting polychromatic phase-contrast imaging, a method for contrast enhancement in transmitted neutron beams by measuring a sample made with a homogeneous material but exhibiting a different microstructure induced by mechanical actions. We were able to reveal the armourers' marks now obscured by polishing that are present in these examples of medieval armour.